Laparoscopic Removal of a Congenital Seminal Vesicle Cyst in Zinner's Syndrome - Jarzemski, Piotr (Society of Laparoendoscopic Surgeons, 2014)
INTRODUCTION: Seminal vesicle cysts are rarely diagnosed, but symptomatic congenital seminal vesicle cysts are reported in the literature describing Zinner syndrome. CASE DESCRIPTION: We present the case of a 26-year-old patient admitted to the urology department because of abdominal pain. A left seminal vesicle cyst and left kidney agenesis were found on examination, and the patient qualified for laparoscopic removal of the left seminal vesicle cyst. The procedure was performed with transperitoneal access using 5 trocars. The peritoneum was incised between the bladder and the rectum to reveal the left seminal vesicle, which was resected from the surrounding tissue. A TachoSil (Takeda Pharmaceuticals, Zurich, Switzerland) hemostatic sponge was placed in the ledge after cutting the base of the seminal vesicle. DISCUSSION: The aim of this study was to evaluate usefulness of the laparoscopic technique to remove a cystic seminal vesicle. The procedure lasted 180 minutes, and the estimated blood loss was 50 mL. We did not record any intra- or postoperative complications. The patient was discharged from the hospital on the third postoperative day and remains symptom-free after 12 months. Histopathologic examination confirmed the presence of a seminal vesicle cyst, and renal agenesis and stenosis of the vas deferens suggests Zinner syndrome. Symptomatic seminal vesicle cysts are a good indication for the application of a laparoscopic technique and, in our opinion, this is better than the open technique because of the view into the surgical area. Therefore, it should be used as the method of choice in treating seminal vesicle defects.